Kant, Freud, and the ethical critique of religion - DiCenso, James J. (International journal for philosophy of religion, 2007)
This paper engages Freud’s relation to Kant, with specific reference to each theorist’s articulation of the interconnections between ethics and religion. I argue that there is in fact a constructive approach to ethics and religion in Freud’s thought, and that this approach can be better understood by examining it in relation to Kant’s formulations on these topics. Freud’s thinking about religion and ethics participates in the Enlightenment heritage, with its emphasis on autonomy and rationality, of which Kant’s model of practical reason is in many ways exemplary. At the same time, Freud advances Kantian thinking in certain important respects; his work offers a more somatically, socially, and historically grounded approach to the formation of rational and ethical capacities, and hence makes it more compatible with contemporary concerns and orientations that eschew the pitfalls of ahistorical idealist orientations.